Microcrystal aluminum foil blank and preparation method thereof
By using aluminum ingots and intermediate alloy melting, add titanium dioxide laser heat treatment, residue and uniformity treatment, cast rolling and laser impact treatment in the preparation of aluminum foil The problem realizes the preparation of microcrystalline aluminum foil gray with high efficiency and detailed performance, excellent mechanical performance, and good corrosion resistance.
Patent Information
- Application Number
- CN202411460785.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-24
AI Technical Summary
The alloy components of existing microcrystalline aluminum foils need to be precisely controlled, and there are problems with tissue segregation and grain control during the preparation process. The traditional preparation methods are cumbersome and costly, making it difficult to meet the needs of large-scale production.
By melting aluminum ingots with intermediate alloys, add titanium dioxide and perform the first phase of laser thermal treatment, then add alkaline oxide resuscitation agent for residue and uniformity, and then perform cast and rolling and the second phase of laser impact treatment In the end, the microcrystalline aluminum foil billet was obtained through cold rolling, division, and heavy roll.
The efficient refinement of aluminum grains is achieved, the mechanical performance and corrosion resistance of aluminum foil blank are improved, the production process is simplified, and energy consumption and cost are reduced.
Smart Images

Figure BDA0005091808520000081 
Figure BDA0005091808520000131 
Figure BDA0005091808520000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum foil blanks, and in particular, relates to a microcrystalline aluminum foil blank and a preparation method thereof. Background Art
[0002] As the demand for new energy and new materials continues to grow, aluminum foil, as a lightweight, high-strength, corrosion-resistant and conductive metal material, has shown broad application prospects in many fields, especially in the new energy industry, such as lithium-ion batteries, solar panels and energy storage systems. As one of the key materials, the performance of aluminum foil directly affects the overall performance and service life of the product.
[0003] Aluminum foil blank is one of the raw materials for aluminum foil production, mainly composed of high-purity aluminum and a small amount of other metal elements. Its production process includes multiple processes such as raw material preparation, smelting, hot rolling and re-rolling. After precise processing and control, the aluminum foil blank has excellent aluminum properties and surface quality; among them, microcrystalline aluminum foil blank significantly improves the strength, toughness and formability of the material by refining the grains, while maintaining good conductivity and corrosion resistance;
[0004] However, the alloy composition of existing microcrystalline aluminum foil requires precise control of the proportion of each element to obtain the ideal microstructure and performance. Secondly, there are problems such as organizational segregation and grain control in the preparation process. These problems directly affect the final quality of the product. In addition, the traditional preparation method is cumbersome and costly, and it is difficult to meet the needs of large-scale production.
[0005] Therefore, based on the above description, there is an urgent need for a method for preparing a microcrystalline aluminum foil blank with excellent mechanical properties, good corrosion resistance, lower production energy consumption, and lower production cost. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the first object of the present invention is to provide a method for preparing a microcrystalline aluminum foil blank, which can achieve efficient refinement of aluminum grains and obtain a microcrystalline aluminum foil blank with excellent mechanical properties and good corrosion resistance.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for preparing a microcrystalline aluminum foil blank comprises the following steps:
[0009] S1, smelting the aluminum ingot and the master alloy together to obtain a prefabricated metal molten solution;
[0010] S2, adding titanium dioxide to the prefabricated metal molten solution, heating it, and then continuously stirring it under the protection of an inert gas to perform the first stage of laser heat treatment;
[0011] S3, after the first stage laser heat treatment, adding alkaline oxide slag remover to remove slag, followed by homogenization treatment to obtain a blended molten solution;
[0012] S4, the mixed molten solution is subjected to a casting and rolling treatment after the first stage of cooling, and then subjected to a second stage of laser shock treatment after the second stage of cooling, to obtain a cast and rolled coil;
[0013] S5. Cold rolling, slitting and rewinding the cast coil to obtain a finished microcrystalline aluminum foil blank.
[0014] Furthermore, in step S1, the intermediate alloy includes at least one of an aluminum-zinc alloy and an aluminum-copper alloy.
[0015] In the present invention, the aluminum-zinc alloy contains at least 60-70% aluminum and 30-40% zinc by mass percentage; the aluminum-copper alloy contains at least 90-95% aluminum and 5-10% copper; zinc and copper are added in the form of an intermediate alloy to ensure that the elements are evenly distributed in the alloy, thereby evenly improving the strength, hardness, corrosion resistance, etc. of the aluminum foil blank.
[0016] Furthermore, in step S2, the temperature is raised to 800-850°C, and then kept warm. After the temperature is constant in this range, the first stage of laser heat treatment is performed, during which continuous stirring is performed at a stirring speed of 200-250 r / min.
[0017] In the present invention, by adopting the first stage laser heat treatment, the titanium dioxide in the prefabricated metal molten solution can be quickly melted to produce a phase change, thereby facilitating the formation of Al3Ti particles with a face-centered cubic lattice as a heterogeneous core. The heterogeneous core has a low mismatch with the aluminum atomic lattice, and thus has good interface coherence, which can allow aluminum atoms to quickly attach, thereby improving the plasticity and strength of the aluminum foil blank and reducing defects such as cracks; in addition, before the first stage laser heat treatment, a preliminary heating is performed, combined with a certain stirring speed, which can improve the formation efficiency of Al3Ti particles and promote the uniform and efficient attachment of aluminum atoms; in addition, in the first stage laser heat treatment stage, an inert gas is used as a protective gas, and stirring can be combined to achieve the effect of hydrogen removal, which can further reduce pores and cracks and improve the quality of the aluminum foil blank, and can also save production steps, improve production efficiency, and reduce energy consumption.
[0018] Furthermore, in step S3, the temperature of the homogenization treatment is 700-750° C., the stirring speed is 400-500 r / min, and the stirring time is 1.5-2 hours.
[0019] Furthermore, in step S4, inert gas is also used for protection in the second stage of laser shock processing, and the inert gas can specifically be argon or nitrogen.
[0020] Furthermore, the alkaline oxide deslagging agent contains at least one of calcium oxide, sodium oxide and magnesium oxide.
[0021] By using alkaline oxide slag remover, impurities in the charge can be better removed and the flow of molten aluminum can be promoted.
[0022] Furthermore, the master alloy accounts for 0.2-0.6% of the prefabricated molten metal solution by mass percentage.
[0023] Furthermore, in step S2, the dosage of the titanium dioxide is 10-15% of the prefabricated molten metal solution by mass percentage.
[0024] Further, in step S2, the laser for the first stage laser heat treatment is an infrared laser, the power of the first stage laser heat treatment is 1200-1500W, the beam scanning speed is 1-3 mm / s, the defocus is 30 mm, and the processing frequency is 10 times / min.
[0025] In the present invention, an infrared laser is used, which has good penetrability and can efficiently heat treat titanium dioxide in a prefabricated metal molten solution, thereby improving the formation efficiency of Al3Ti particles and the attachment efficiency of aluminum atoms, thereby further reducing the grain size in the prefabricated metal molten solution, thereby increasing the grain boundary area, enhancing the hindering effect of the grain boundary on dislocation movement, and improving the strength and toughness of the material.
[0026] Furthermore, in step S3, the amount of the basic oxide deslagging agent added is 0.2-0.4% by mass of the prefabricated molten metal solution.
[0027] Furthermore, in step S4, after the second stage of cooling, the temperature of the blended molten solution is reduced to 100-150°C.
[0028] Furthermore, in step S4, the laser used in the second stage of laser shock treatment is an infrared laser, the pulse width of the second stage of laser shock treatment is 15 ns, and the pulse energy is 2-5 GW / cm 2 , the spot diameter is 2mm, the number of impacts is 5-10 times, and the constraint layer is 150-200μm.
[0029] In the present invention, the constrained layer is flowing water or glass commonly used in the art; through the second stage laser shock treatment, the Al3Ti with aluminum atoms attached can be compressed by generating high-pressure shock waves, thereby reducing the lattice constant of aluminum atoms and Al3Ti, and further improving the interface coherence between the two, thereby improving the hardness and fatigue resistance of the cast coil.
[0030] Furthermore, in step S4, the front box temperature of the casting and rolling process is 700-710°C, the cooling water temperature is 35-45°C, the casting and rolling zone temperature is 55-65°C, the strip speed is 800-900mm / min, and the thickness of the cast and rolled coil is 6-6.5mm.
[0031] The second object of the present invention is to provide a microcrystalline aluminum foil blank prepared by the above method.
[0032] The beneficial effects of the present invention are:
[0033] (1) The present invention adopts the first stage laser heat treatment to quickly melt the titanium dioxide in the prefabricated metal molten solution to produce a phase change, thereby facilitating the formation of Al3Ti particles with a face-centered cubic lattice as a heterogeneous core. The heterogeneous core has a low mismatch with the aluminum atomic lattice, and thus has good interface coherence, which allows aluminum atoms to attach quickly, thereby improving the plasticity and strength of the aluminum foil blank, reducing defects such as cracks, and thereby improving its mechanical properties such as elongation and tensile strength, as well as its corrosion resistance.
[0034] (2) The present invention performs a preliminary heating before the first stage laser heat treatment, and with a certain stirring speed, can improve the formation efficiency of Al3Ti particles and promote the uniform and efficient attachment of aluminum atoms;
[0035] (3) In the first stage of laser heat treatment, inert gas is used as the protective gas, and stirring can be combined to achieve the effect of hydrogen removal, which can not only further reduce pores and cracks and improve the quality of aluminum foil blanks, but also save production steps, improve production efficiency, reduce energy consumption, and reduce costs. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] Example 1
[0038] This embodiment provides a method for preparing a microcrystalline aluminum foil blank, comprising the following steps:
[0039] 1. Melting and preparation of prefabricated metal molten solution
[0040] (1) Raw material preparation: Select high-purity aluminum ingots as the main raw material, and prepare an appropriate amount of aluminum-zinc alloy (60% aluminum, 40% zinc) as an intermediate alloy; wherein the amount of aluminum-zinc alloy added is 0.4% by mass of the prefabricated metal molten solution.
[0041] (2) Smelting process: Aluminum ingots and aluminum-zinc alloy are placed in a smelting furnace and heated until completely melted. During this period, mechanical stirring is used to ensure that the alloy components are evenly mixed to obtain a prefabricated metal molten solution.
[0042] 2. Titanium dioxide addition and first stage laser heat treatment
[0043] (1) Adding titanium dioxide: Add titanium dioxide powder accounting for 12% of the total mass of the solution to the prefabricated molten metal solution, continue heating to 800°C, and maintain near this temperature.
[0044] (2) Inert gas protection: During the entire addition and heating process, argon gas is continuously introduced to prevent oxidation of the molten solution.
[0045] (3) First stage laser heat treatment: The molten solution was subjected to laser heat treatment using an infrared laser. The laser power was set to 1350 W, the beam scanning speed was 2 mm / s, the defocus was adjusted to 30 mm, and the treatment was performed 10 times per minute. During the laser heat treatment process, the stirring speed was maintained at 220 r / min, and at the same time, the hydrogen was stirred out with the help of an inert gas.
[0046] 3. Slag removal and homogenization treatment
[0047] (1) Deslagging: After the first stage of laser heat treatment, 0.3% of the total mass of the solution was added to the molten solution, and the scum was skimmed off after standing for a period of time.
[0048] (2) Homogenization treatment: The molten solution after slag removal is stirred and cooled in a smelting furnace so that the solution composition and temperature reach a uniform state of 750°C to obtain a blended molten solution.
[0049] 4. Casting and second stage laser shock treatment
[0050] (1) Casting and rolling treatment: The blended molten solution was poured into the pouring system of the casting and rolling machine, and the front box temperature was controlled to be 705°C, the cooling water temperature was 40°C, the casting and rolling zone temperature was 60°C, and the strip speed was 850 mm / min. After the casting and rolling treatment, a cast and rolled coil with a thickness of 6.2 mm was obtained.
[0051] (2) Second stage of cooling: The cast coil is taken out of the casting mill and cooled to 120°C.
[0052] (3) Second stage laser shock treatment: The cooled cast coil is subjected to laser shock treatment using an infrared laser with a pulse width of 15 ns and a pulse energy of 3 GW / cm 2 , the spot diameter is 2 mm, each position is impacted 7 times, and the constrained layer thickness is 175 microns.
[0053] 5. Preparation of finished microcrystalline aluminum foil blanks
[0054] The cast coil was cold rolled for 7 times, and finally a microcrystalline aluminum foil blank with a thickness of 0.24 mm was obtained by combining uniform withdrawal, rewinding and longitudinal cutting. The specific operating parameters are shown in the following table:
[0055] Table 1
[0056]
[0057] Example 2
[0058] 1. Melting and preparation of prefabricated metal molten solution
[0059] (1) Raw material preparation: Select high-purity aluminum ingots as the main raw material, and prepare an appropriate amount of aluminum-copper alloy (93% aluminum, 7% zinc) as an intermediate alloy; wherein the amount of aluminum-copper alloy added is 0.4% by mass of the prefabricated metal molten solution.
[0060] (2) Smelting process: Aluminum ingots and aluminum-zinc alloy are placed in a smelting furnace and heated until completely melted. During this period, mechanical stirring is used to ensure that the alloy components are evenly mixed to obtain a prefabricated metal molten solution.
[0061] 2. Titanium dioxide addition and first stage laser heat treatment
[0062] (1) Titanium dioxide addition: Add titanium dioxide powder accounting for 13% of the total mass of the solution into the prefabricated metal molten solution, continue heating to 820°C, and maintain near this temperature.
[0063] (2) Inert gas protection: During the entire addition and heating process, nitrogen is continuously introduced to prevent oxidation of the molten solution.
[0064] (3) The first stage of laser heat treatment: The molten solution was subjected to laser heat treatment using an infrared laser. The laser power was set to 1450 W, the beam scanning speed was 1 mm / s, the defocus was adjusted to 30 mm, and the treatment was performed 10 times per minute. During the laser heat treatment process, the stirring speed was maintained at 200 r / min to ensure uniform distribution of laser energy. At the same time, hydrogen was stirred out with the help of inert gas.
[0065] 3. Slag removal and homogenization treatment
[0066] (1) Deslagging: After the first stage of laser heat treatment, 0.5% of the total mass of the solution was added to the molten solution, and the slag was skimmed off after standing for a period of time.
[0067] (2) Homogenization treatment: The molten solution after slag removal is stirred and cooled in a smelting furnace so that the solution composition and temperature reach a uniform state of 720°C to obtain a blended molten solution.
[0068] 4. Casting and second stage laser shock treatment
[0069] (1) Casting and rolling treatment: Pour the blended molten solution into the pouring system of the casting and rolling machine, control the front box temperature to 702°C, the cooling water temperature to 40°C, the casting and rolling zone temperature to 55°C, and the strip speed to 880 mm / min. After the casting and rolling treatment, a cast and rolled coil with a thickness of 6.5 mm is obtained.
[0070] (2) Second stage of cooling: The cast coil is taken out of the casting mill and cooled to 100°C.
[0071] (3) Second stage laser shock treatment: The cooled cast coil is subjected to laser shock treatment using an infrared laser with a pulse width of 15 ns and a pulse energy of 3 GW / cm 2 , the spot diameter is 2 mm, each position is impacted 5 times, and the constrained layer thickness is 150 microns.
[0072] 5. Preparation of finished microcrystalline aluminum foil blanks
[0073] The cast coil was cold rolled for 7 passes, and finally a microcrystalline aluminum foil blank with a thickness of 0.24 mm was obtained by combining uniform withdrawal, recoiling and longitudinal cutting. The processing parameters were the same as those in Table 1.
[0074] Example 3
[0075] 1. Melting and preparation of prefabricated metal molten solution
[0076] (1) Raw material preparation: Select high-purity aluminum ingots as the main raw material, and prepare an appropriate amount of aluminum-zinc alloy (70% aluminum, 30% zinc) as an intermediate alloy; wherein the amount of aluminum-zinc alloy added is 0.6% by mass of the prefabricated metal molten solution.
[0077] (2) Smelting process: Aluminum ingots and aluminum-zinc alloy are placed in a smelting furnace and heated until completely melted. During this period, mechanical stirring is used to ensure that the alloy components are evenly mixed to obtain a prefabricated metal molten solution.
[0078] 2. Titanium dioxide addition and first stage laser heat treatment
[0079] (1) Adding titanium dioxide: Add titanium dioxide powder accounting for 15% of the total mass of the solution to the prefabricated molten metal solution, continue heating to 850°C, and maintain near this temperature.
[0080] (2) Inert gas protection: During the entire addition and heating process, nitrogen is continuously introduced to prevent oxidation of the molten solution.
[0081] (3) The first stage of laser heat treatment: The molten solution was subjected to laser heat treatment using an infrared laser. The laser power was set to 1250 W, the beam scanning speed was 1 mm / s, the defocus was adjusted to 30 mm, and the treatment was performed 10 times per minute. During the laser heat treatment process, the stirring speed was maintained at 250 r / min to ensure uniform distribution of laser energy. At the same time, hydrogen was stirred out with the help of inert gas.
[0082] 3. Slag removal and homogenization treatment
[0083] (1) Deslagging: After the first stage of laser heat treatment, 0.5% of the total mass of the solution was added to the molten solution, and the slag was skimmed off after standing for a period of time.
[0084] (2) Homogenization treatment: The molten solution after slag removal is stirred and cooled in a smelting furnace so that the solution composition and temperature reach a uniform state of 720°C to obtain a blended molten solution.
[0085] 4. Casting and second stage laser shock treatment
[0086] (1) Casting and rolling treatment: The blended molten solution was poured into the pouring system of the casting and rolling machine, and the front box temperature was controlled to be 702°C, the cooling water temperature was 35°C, the casting and rolling zone temperature was 65°C, and the strip speed was 850 mm / min. After the casting and rolling treatment, a cast and rolled coil with a thickness of 6.2 mm was obtained.
[0087] (2) Second stage of cooling: The cast coil is taken out of the casting mill and cooled to 120°C.
[0088] (3) Second stage laser shock treatment: The cooled cast-rolled coil is subjected to laser shock treatment using an infrared laser. The pulse width is set to 15 ns, the pulse energy is 5 GW / cm2, the spot diameter is 2 mm, each position is shocked 10 times, and the constrained layer thickness is 150 μm.
[0089] 5. Preparation of finished microcrystalline aluminum foil blanks
[0090] The cast coil was cold rolled for 7 passes, and finally a microcrystalline aluminum foil blank with a thickness of 0.24 mm was obtained by combining uniform withdrawal, recoiling and longitudinal cutting. The processing parameters were the same as those in Table 1.
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 1 is that no intermediate alloy is used.
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 1 is that the first stage laser heat treatment is not performed, and the temperature is raised to 1200° C. after titanium dioxide is added and maintained near this temperature, during which stirring is continued at a stirring speed of 250 r / min.
[0095] Comparative Example 3
[0096] The difference between this comparative example and Example 1 is that before the first stage of laser heat treatment, aluminum-titanium alloy (85% aluminum and 15% titanium by mass percentage) is added, but the temperature is raised to 1600°C and maintained near this temperature, during which stirring is continued at a stirring speed of 250 r / min.
[0097] Comparative Example 4
[0098] The difference between this comparative example and Example 1 is that titanium dioxide is not added.
[0099] Comparative Example 5
[0100] The second stage laser shock treatment was not performed, and the cast-rolled coil after the cast-rolling treatment and the second stage cooling treatment was further used to prepare the finished microcrystalline aluminum foil blank.
[0101] Comparative Example 6
[0102] The difference between this comparative example and Example 1 is that the first stage laser heat treatment and the second stage laser shock treatment are not performed.
[0103] Test Example 1
[0104] The tensile strength and elongation of the 0.24 mm thick microcrystalline aluminum foil blanks prepared in Examples 1-3 and Comparative Examples 1-6 were tested. The tensile test was performed in accordance with GB / T 228 "Room Temperature Tensile Test Method for Metallic Materials" to measure the tensile strength and elongation of the aluminum foil. The test results are shown in Table 2 below.
[0105] Test Example 2
[0106] The 0.24 mm thick microcrystalline aluminum foil blanks prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to corrosion performance testing, specifically referring to JIS Z 2371 "Salt Spray Test Method" for corrosion resistance testing. The test results are shown in Table 2 below.
[0107] Table 2
[0108]
[0109]
[0110] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a microcrystalline aluminum foil blank, characterized in that: The following steps are involved: S1, smelting the aluminum ingot and the master alloy together to obtain a prefabricated metal molten solution; S2, adding titanium dioxide to the prefabricated metal molten solution, heating it, and then continuously stirring it under the protection of an inert gas to perform the first stage of laser heat treatment; S3, after the first stage laser heat treatment, adding alkaline oxide slag remover to remove slag, followed by homogenization treatment to obtain a blended molten solution; S4, the mixed molten solution is subjected to a casting and rolling treatment after the first stage of cooling, and then subjected to a second stage of laser shock treatment after the second stage of cooling, to obtain a cast and rolled coil; S5. Cold rolling, slitting and rewinding the cast coil to obtain a finished microcrystalline aluminum foil blank.
2. The method for preparing the microcrystalline aluminum foil blank according to claim 1, characterized in that: In step S1, the master alloy includes at least one of an aluminum-zinc alloy and an aluminum-copper alloy.
3. The method for preparing the microcrystalline aluminum foil blank according to claim 2, characterized in that: In terms of mass percentage, the master alloy accounts for 0.2-0.6% of the prefabricated molten metal solution.
4. The method for preparing the microcrystalline aluminum foil blank according to claim 1, characterized in that: In step S2, the amount of titanium dioxide added is 10-15% of the prefabricated molten metal solution by mass percentage.
5. The method for preparing the microcrystalline aluminum foil blank according to claim 1, characterized in that: In step S2, the laser used in the first stage of laser heat treatment is an infrared laser, the power of the first stage of laser heat treatment is 1200-1500W, the beam scanning speed is 1-3 mm / s, the defocus is 30 mm, and the processing frequency is 10 times / min.
6. The method for preparing a microcrystalline aluminum foil blank according to claim 1, characterized in that: In step S3, the amount of the basic oxide deslagging agent added is 0.2-0.4% by mass of the prefabricated molten metal solution.
7. The method for preparing a microcrystalline aluminum foil blank according to any one of claims 1 to 6, characterized in that: In step S4, after the second stage of cooling, the temperature of the blended molten solution is reduced to 100-150°C.
8. The method for preparing the microcrystalline aluminum foil blank according to claim 7, characterized in that: In step S4, the laser used in the second stage of laser shock treatment is an infrared laser, the pulse width of the second stage of laser shock treatment is 15ns, and the pulse energy is 2-5GW / cm 2, The spot diameter is 2mm, the number of impacts is 5-10 times, and the constraint layer is 150-200 microns.
9. The method for preparing a microcrystalline aluminum foil blank according to claim 1, characterized in that: In step S4, the front box temperature of the casting and rolling treatment is 700-710°C, the cooling water temperature is 35-45°C, the casting and rolling zone temperature is 55-65°C, the strip speed is 800-900mm / min, and the thickness of the cast and rolled coil is 6-6.5mm.
10. A microcrystalline aluminum foil blank prepared by the method for preparing a microcrystalline aluminum foil blank according to any one of claims 1 to 9.